Analisis Pengaruh Budaya, Sosial, Kepribadian dan Psikologis terhadap Keputusan Pembelian HP Merk Apple - M. Azizul Khakim; Selvira Medina (CV. Strata Persada Academia, 2023)
This study aims to identify and analyze the sosial, cultural, personality and psychological influences that have a significant effect on Apple brand mobile phone purchasing decisions. This research is a quantitative research conducted using the comparative casual method, which is a type of research with the characteristics of a causal relationship problem between two or more variabel. The population in this study are all customers who have used the Apple cellphone brand. The sampling technique was carried out by accidental sampling and the number of samples was 100 people. Data analysis techniques were performed using multiple regression analysis. The results of the study show that culture has a significant and positive influence on purchasing decisions for Apple brand mobile phones. Sosial has a positive effect on purchasing decisions for Apple brand mobile phones. Personality has a positive effect on purchasing decisions for Apple brand mobile phones. Psychology has a positive influence on purchasing decisions for apple mobile phones.